A method to derive global O/N2 ratios from SSUSI/DMSP based on Re-AURIC algorithm. (March 2020) - Ding, GuangXing; Chen, Bo; Zhang, XiaoXin; He, Fei
Abstract: Global thermospheric O/N2 column density ratios are obtained using the SSUSI/DMSP far-ultraviolet (FUV) dayglow data and the Re-AURIC simulation results. The Re-AURIC is derived from the AURIC algorithm after some old modules are updated. The calculation processes of O/N2 ratio are then established using the simulations of Re-AURIC to calibrate the ratios of the OI 135.6 nm emission and N2 LBHS emission from SSUSI observations. The standard deviation (1 σ ) and correlation coefficient are 0.045 and 0.769 compared with the O/N2 ratios provided by the SSUSI EDR data. The statistical errors between the calculated ratios and the EDR references are generally less than 0.2 with 96.40% at 2 σ (95.44%) and less than 0.1 with 60.51% at about 1 σ (68.26%). Two global O/N2 ratio maps are obtained using this method to study its variations when the magnetic storm occurs. The significant O/N2 depletion can be seen in one O/N2 ratio map whose K p index is 6. Also, the depletion is not uniform at different longitudes and the scales extend from high latitude to low latitude during magnetic storm. This proposed method provides us with a simple and useful tool to obtain the global O/N2 distribution and even the future modeling from the observations on satellites. Highlights: The Re-AURIC algorithm can be applied to the present calculation and the initial inputs are only three parameters. The O/N2 ratio in atmosphere is basically linear with the observed FUV dayglow OI 135.6 and LBHS. The statistical errors are less than 0.2 with 96.40% at 2σ (95.44%) and less than 0.1 with 60.51% at about 1σ (68.26%). The significant O/N2 depletion can be seen when the geomagnetic activity is disturbed and the depletion is not uniform.